Development of the Canadian food intake screener for adolescents based on Canada’s Food Guide 2019 healthy eating recommendations - Tugault-Lafleur, Claire; Desgreniers, Virginie; Bessette, Geneviève; Kazzi, Rita A.; Jacob, Raphaëlle; Hernandez, Kimberley; St-Pierre, Sylvie; Haines, Jess (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Assessing adolescents’ dietary intakes in relation to Canada’s Food Guide 2019 (CFG-2019) recommendations on healthy food choices is a critical component to public health surveillance efforts. The study aimed to develop a brief self-administered screener to assess food intake based on CFG-2019 food choices recommendations among English- and French-speaking adolescents aged 10–17 years living in Canada. Methods The development and assessment of the content validity of the tool was undertaken in collaboration with Health Canada advisors and informed by external content experts, including nutrition researchers and practitioners. Following a rapid review of screeners used among children aged 6–17 years, an initial draft was developed, and content validity was assessed by an expert panel with expertise in public health nutrition and questionnaire validation (English n = 13, French n = 7). Two rounds of cognitive interviews were then conducted with adolescents (English n = 15, French n = 14) to assess comprehension and further refine the screener items. Cognitive testing using a direct probing approach was conducted iteratively in two phases to assess understanding of questions and incorporate feedback from adolescents to improve the clarity and wording of the items at each phase. Results Following the expert panel and iterative discussions with Health Canada advisors, four items were removed from the initial 14-item screener as these items were deemed not sufficiently reflective of the CFG recommendations and one item asking about water intake was tested. Cognitive testing revealed that the items were well understood overall, and feedback at each interview round enabled additional refinements to improve comprehension. The resulting screener includes 10 items designed to rapidly assess food intake based on CFG-2019 recommendations on healthy food choices for adolescents aged 10 to 17 years. Conclusions The Canadian Food Intake Screener for Adolescents/Questionnaire court canadien sur les apports alimentaires des adolescents is designed to rapidly assess dietary intake over the past week among children aged 10 to 17 years. Before it can be used for research and population-level nutrition surveillance, further research is needed to develop a scoring system and evaluate the screener’s construct validity and reliability.